The study of the method of the direct torque control based on space vector pulse width modulation - Shihao, Ruan; Weiting, LIU; Haifeng, Wei; Pengyu, Yan; Jinyi, Yao; Jiaqi, Chen (IJRDO - Journal of Electrical And Electronics Engineering, 2018)
The paper expounds the mathematical model of permanent magnet synchronous motor, which introduces the general principle of the direct torque control and the space vector pulse width modulation. In the MATLAB/simulink environment, the mathematical model of permanent magnet synchronous motor sets up a simulation model of the direct torque control which based on the theory of SVPWM. Each step and process of the simulation model is introduced in detail and finally the simulation result is obtained. The simulation result shows that the direct torque control system which based on the theory of SVPWM has a constant switch frequency, can reduce the torque ripple greatly, and improves the current waveform and flux linkage waveform. So it makes the system have a better dynamic and static performance and  also verify the feasibility and effectiveness of the plan